Vegetative anatomy of Calypsoeae (Orchidaceae) - Carlsward, Barbara (Universidad de Costa Rica, 2008)
Calypsoeae represent a small tribe of anatomically little-known orchids with a wide distribution in the Western Hemisphere. Leaves are present in all genera, except Corallorhiza and Wullschlaegelia both of which are subterranean taxa. Stomata are abaxial (ad- and abaxial in Aplectrum) and tetracytic (anomocytic in Calypso). Fiber bundles are absent in leaves of all taxa examined except Govenia tingens. Stegmata are present in leaves of only Cremastra and Govenia. Roots are velamentous, except in filiform roots of Wullschlaegelia. Vegetative anatomy supports a relationship between Wullschlaegelia and Corallorhiza but does not support the grouping of winter-leaved Aplectrum and Tipularia nor proposed groupings of genera based on pollinarium features.